2012
DOI: 10.1103/physreve.86.031129
|View full text |Cite
|
Sign up to set email alerts
|

Depinning phase transition in the two-dimensional clock model with quenched randomness

Abstract: With Monte Carlo simulations, we systematically investigate the depinning phase transition in the two-dimensional driven random-field clock model. Based on the short-time dynamic approach, we determine the transition field and critical exponents. The results show that the critical exponents vary with the form of the random-field distribution and the strength of the random fields, and the roughening dynamics of the domain interface belongs to the new subclass with ζ≠ζ(loc)≠ζ(s) and ζ(loc)≠1. More importantly, w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Besides, two-dimensional spin models, as Ising, XY, and Heisenberg, have been adapted for the study of creep and depinning in domain wall motion [15][16][17][18][19][20]. Such spatial models permit indeed to simulate bubble domains and domains with overhangs, but their intrinsic periodic pinning made these models not truly realistic or comparable to the experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, two-dimensional spin models, as Ising, XY, and Heisenberg, have been adapted for the study of creep and depinning in domain wall motion [15][16][17][18][19][20]. Such spatial models permit indeed to simulate bubble domains and domains with overhangs, but their intrinsic periodic pinning made these models not truly realistic or comparable to the experiments.…”
Section: Introductionmentioning
confidence: 99%
“…( 31), taking f and g given by Eqs. (33) and (34) into Eq. ( 2), then u and v are two two-rogue waves.…”
Section: Multi-rogue Wave Solutions With N =mentioning
confidence: 99%
“…The realm of multicomponent BECs with optical dipole trap leads to realising the spinor BECs (see review article [4] and references therein). For a generic hyperfine spin F = 1 state, the spinor solitons in a one-dimensional coupled Gross-Pitaevskii (GP) system have been studied theoretically [5][6][7] and matter rogue waves have been investigated [8]. Indeed, pertinent experimental works have shown that the creation of mixed type dark-bright-bright and dark-dark-bright solitons and magnetic solitons in spin-1 BECs [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%